Packaging for sustainability - Fitzpatrick, Leanne; Lewis, Helen; Verghese, Karli (Springer, 2012)
This concise and readable handbook for practitioners who are trying to implement sustainability strategies for packaging deploys industry case studies throughout to illustrate possible applications and scenarios in a sector under growing regulatory pressure